2022
DOI: 10.1021/acs.jpca.2c04354
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Simulation on Regulating the Magnetic Coupling Properties of Diradical Artificial Bases

Abstract: In this work, we computationally designed a series of diradical molecules with obvious magnetic coupling properties based on newly synthesized artificial bases, 6-amino-3-(1′-β-d-2′-deoxyribofuranosyl)-5-nitro-1H-pyridin-2-one (Z), 2-amino-8-(1′-β-d-2′-deoxyribofuranosyl)-imidazo-[1,2a]-1,3,5-triazin-[8H]-4-one (P), 6-amino-9[(1′-β-d-2′-deoxyribofuranosyl)-4-hydroxy-5-(hydroxymethyl)-oxolan-2-yl]-1H-purin-2-one (B), and found two methods (base pairing and nitro group rotation) of regulating the magnetic magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…A significant number of recent research studies ,,, , have been dedicated to finding new strategies for designing new organic diradicals with unique magnetic properties, especially in chemical processes that change or modify the magnetic properties of systems when transitions from ferromagnetic (FM) to antiferromagnetic (AFM) coupling (or vice versa) or when significant changes in the magnitude of the magnetic coupling constant J are observed. For example, Malik and Bu have shown that intramolecular proton transfer is able to modulate the magnetic spin-coupling interaction in photochromic azobenzene derivatives with ortho -site hydroxyl as a modulator, where some molecules can undergo magnetic conversion between antiferromagnetic and ferromagnetic coupling due to proton-transfer processes exhibiting large changes in J values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of recent research studies ,,, , have been dedicated to finding new strategies for designing new organic diradicals with unique magnetic properties, especially in chemical processes that change or modify the magnetic properties of systems when transitions from ferromagnetic (FM) to antiferromagnetic (AFM) coupling (or vice versa) or when significant changes in the magnitude of the magnetic coupling constant J are observed. For example, Malik and Bu have shown that intramolecular proton transfer is able to modulate the magnetic spin-coupling interaction in photochromic azobenzene derivatives with ortho -site hydroxyl as a modulator, where some molecules can undergo magnetic conversion between antiferromagnetic and ferromagnetic coupling due to proton-transfer processes exhibiting large changes in J values.…”
Section: Introductionmentioning
confidence: 99%
“…The quest for designing and understanding novel organic compounds that can be characterized as open-shell singlet or triplet electronic spin states exhibiting unique properties that can be applied for various practical applications (spintronics, quantum information science, organic electronics) has long been of considerable interest to researchers. Some of the most important characteristics describing organic compounds include their stability, optical and magnetic properties, and degree of reactivity. , Thus, many theoretical and computational models for predicting such properties have been developed over many years for the purpose of accurately describing the electronic structures of such systems. In this context, some of the most useful concepts for understanding organic systems are aromaticity, the degree of diradical character, and magnetic properties. To this end, various descriptors for evaluating the degree of aromaticity have been developed, as well as various measures of diradica...…”
Section: Introductionmentioning
confidence: 99%
“…For a diradical, when two unpaired electrons occupy nearly degenerate spatial orbitals, a parallel-spin orientation gives rise to a triplet ground state (ferromagnetic coupling) while an antiparallel-spin orientation leads to a singlet ground state (antiferromagnetic coupling) [7]. A common type of organic diradical is composed of two single radical groups as the spin sources bridging through a coupler, which has been extensively investigated experimentally and theoretically [8][9][10][11][12][13][14][15][16][17][18]. The magnetic coupling constant J is largely dependent on the interaction between two spin sources.…”
Section: Introductionmentioning
confidence: 99%